Features of the combined flow of pulmonary tuberculosis and diabetes mellitus - A.S. Shalmin; E.N. Raznatovskaya; Yu.M. Bobrovnichaya-Dvizova; A.V. Dvizov; N.V. Malyar; T.S. Fedchenko (Zaporozhye State Medical University, 2012)
The aim of the study was to investigate the features of the course, clinical manifestations, diagnosis and treatment of the combination of pulmonary tuberculosis and diabetes mellitus.